2019
DOI: 10.1088/1748-9326/ab465f
|View full text |Cite
|
Sign up to set email alerts
|

A surface modelling approach for attribution and disentanglement of the effects of global warming from urbanization in temperature extremes: application to Lisbon

Abstract: Attribution and disentanglement of the effects of global greenhouse gas and land-use changes on temperature extremes in urban areas is a complex and critical issue in the context of regional-to-local climate change mitigation and adaptation. Here, an innovative modelling framework based on a large ensemble of urban climate simulations, using SURFEX (a land-surface model) coupled to TEB (an urban canopy model), forced by E20C (a GCM-based reanalysis), is proposed, and applied to the capital of Portugal-Lisbon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…9f shows that reducing the roughness length for heat transfer by a factor of 10 for highvegetation types directly in simulation CTR resulted in an overall increase in the errors over most of Iberia (particularly over all regions that were dominated by high vegetation in CTR). Other surface parameters also play an important role in simulated surface temperature, such as albedo and emissivity, which are also related to the surface vegetation coverage in LSMs (e.g., Nogueira and Soares, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…9f shows that reducing the roughness length for heat transfer by a factor of 10 for highvegetation types directly in simulation CTR resulted in an overall increase in the errors over most of Iberia (particularly over all regions that were dominated by high vegetation in CTR). Other surface parameters also play an important role in simulated surface temperature, such as albedo and emissivity, which are also related to the surface vegetation coverage in LSMs (e.g., Nogueira and Soares, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its widespread emergence in urban environments, the UHI is sensitive to the specific land surface characteristics and meteorological conditions, hence displaying significant variability between different locations and periods. Indeed, previous investigations reported several different relevant UHI dependencies, including city size and population density (Oke, 1982;Clinton & Gong, 2013;Manoli et al, 2019), urban vegetation coverage (Kaloustian & Diab, 2015;Peng et al, 2012;Zhou et al, 2014;Nogueira & Soares, 2019), background climate conditions (namely precipitation and wind, Zhou et al, 2013;Zhao et al, 2014;Manoli et al, 2019) and urban morphology (e.g., city geometry, building height, construction materials, etc., Oke, 1973;1982;Zhou et al, 2017;Krayenhoff et al, 2018;Nogueira & Soares, 2019;Masson et al, 2020). Heat release resulting from human activities has also been shown to modulate the UHI (De Munck et al, 2013;Schoetter et al, 2020).…”
mentioning
confidence: 99%
“…One may estimate the urban impact on surface and near-surface air temperature and humidity, near-surface wind, latent and sensible heat fluxes, but not on clouds, precipitation, or local circulations. Despite those limitations, recent studies have demonstrated the added value of this approach in reproducing key features of observed urban climate compared to traditional climate simulations (without representation of urban processes), including the UHI and the frequency, intensity and duration of urban extreme temperature events (Broadbent et al, 2018;Conlon et al, 2016;Daniel et al, 2018;Kaloustian and Diab, 2015;Lemonsu et al, , 2015Nogueira and Soares, 2019;Hamdi et al, 2020;Viguié et al, 2020;Nogueira et al, 2020b). Leveraging the competitive computational cost of offline LSM-UCM simulations, these studies explored the local climate response to multiple different urbanization patterns and emission scenarios over relatively long periods and at high spatial resolution.…”
mentioning
confidence: 99%
See 2 more Smart Citations